Prevalence, Severity, and Risk Factors of Neurodevelopmental Delay in Children with Cyanotic Versus Acyanotic CHD in Pakistan: A Cross-Sectional Study: Prevalence, Severity, and Risk Factors of Neurodevelopmental Delay in Children - Ahmad, Iftikhar; Zafar, Muhammad Adnan; Rehman, Fazal Ur; Munir, Ussama; Shafiq, Umar (Pakistan Journal of Health Sciences, 2025)
Children with congenital heart disease (CHD) are at increased risk of neurodevelopmental delay due to chronic hypoxemia and associated medical complexities. Measurement of this burden is critical in determining early intervention. Objectives: To compare the prevalence, severity, and risk factors of neurodevelopmental delay between cyanotic and acyanotic CHD in a Pakistani cohort. Methods: This cross-sectional study was conducted at the Department of Paediatric Cardiology, Quaid-e-Azam Medical College, Bahawalpur, from December 2023 to May 2025. A non-probability consecutive sample of 316 children, aged 6 months to 10 years, was recruited. Neurodevelopment was assessed using the Denver II and Ages & Stages Questionnaires-3 (ASQ-3), administered by trained assessors with inter-rater calibration. Cyanotic CHD and acyanotic CHD were verified by the use of echocardiography. Results: The mean age of participants was 4.2 ± 2.1 years; 178 (56.3%) were male. Developmental delay was identified in 186 children (58.9%), more frequent in cyanotic CHD (70.9%) than acyanotic CHD (46.8%) (χ²=18.7, p<0.001). Cyanotic CHD (OR 2.83, 95% CI: 1.77–4.51), male sex (OR 1.52, 95% CI: 1.01–2.31), low oxygen saturation <85% (OR 3.21, 95% CI: 2.08–4.95), and age <5 years (OR 1.66, 95% CI: 1.11–2.49) were independent predictors. Lower oxygen saturation correlated with greater delay severity (Spearman’s ρ=-0.46, p<0.001). Conclusions: Neurodevelopmental delay is very common in children with CHD, especially in cyanotic defects and hypoxemia. A routine developmental screening and early rehabilitation exercises may be necessary to prevent the long-term deficits.